A experiência dos empreendedores públicos no governo de Minas Gerais: trabalho de formiguinha, tentando tirar água de pedra - Carolina Riente de Andrade (2013)
This dissertation aims at understanding the experience of public entrepreneurs (PE) within Minas Gerais government, from a managers perspective, starting from the program creators and the PEs second generation (2011-2014). This is a partial analysis because it assesses only the first two years of Antonio Anastasia/Alberto Pinto Coelhos government, although searching for the differences in action and perspectives compared to the first generation (2007-2010). It is based on the assumption that the current experience has not presented any rupture in relation to the former one, but it owns some individual features, stemming from both the political changes and the government strategic orientation. Also adopted in this dissertation is the assumption that part of the PEs perception of their situation is due to the behavior of both the position management and its occupants. Therefore, issues were arisen on peoples competence management within the public sector, displaying a bias toward the competence models, which points to the position occupation selection, the agreement on goals and the follow-up of the entrepreneurs individual results. This thesis has seven chapters, from the introduction, in which the research problems and its objectives, both central and specific, are clearly explained. In the second, third and fourth chapters, the theoretical referential is described, featuring three main analysis axis: the HR formation in the creation of Brazilian Public Administration; an overview of the historical building of People Management both in the world and in Brazil, under the approach of Management by Competence, a model that guides the selection and the management of the public entrepreneur, and the public entrepreneurship and entrepreneur. Through the fifth chapter, methodology is constructed and the researchers epistemological position is displayed. In the sixth chapter, the results are presented and analyzed, and, through the seventh chapter, final considerations are formulated. The conclusions point to a majority of individuals having positive perception, adhering to the governments official speech which calls for entrepreneurial actions, involving the mobilization of specific competences. Nevertheless, not all public entrepreneurs present perceptions in line with the official speech, and some of them believe that this position is little different from other public positions, not necessarily of entrepreneurs, and therefore, notfurnishing a suitable answer to the fixed objectives for their action within the Minas Gerais Government. Many of them report a feeling of frustration in face of their expectations in relation to their function. Adding to those discontents, a high rate of dissatisfaction at the tools used by the management, mainly the work planning, exists. In relation to the specificities of the PEs second generation, the results indicate a change in the profile, mainly the growing participation of professionals coming from both the very public sector and the academy, at the expenses of those coming from private companies. The results, therefore, show acombination, or, at least, the connivance between both public and private sector skills. In relation to the development of skills, it was seen that the PEs consider this action as an opportunity for growth and acquisition of new knowledge and experience, besides making it possible to get a deeper knowledge of the public machine and act as technical and political leaders at the state government. Somehow the development of new competences allows for professionals to face management challenges, both political and institutional, within the government, while better preparing them for an occasional return to the private sector.